(untitled) (Fiep Bulletin - online, 2013)
In the contribution we try to bring complex information about origin, history and the present of one of the oldest international physical education organisations – International Federation of Physical Education (FIEP) and its activities in Europe. During elaborating of this material we came out predominantly from historical materials about FIEP, from studies of old as well as present „FIEP Bulletins“, from annual FIEP reports, from FIEP congresses proceedings and other reachable materials about its activity. In this way we also want to thank Robert Decker, former chairman of FIEP Europe section for precious advices and comments during work on this publication. In the contribution we mention all of the most important FIEP personalities from the history and the present. We do not introduce their academic and scientific titles, for we do not succeed to find them exactly and the second reason is that in present the titles are changing relatively in a fast way. Thus we want to avoid eventual inaccuracies at titles introduction. In addition in the FIEP community the quality of people was never judged according academic, scientific, or other titles. The highest guarantee of quality always used to be the name of concrete man and his work, which in favour of physical education and sport development made. Many outstanding FIEP personalities were not engaged on academic and on scientific field, too. For simplification we use in the text many abbreviations, mostly of international organisations. Complete names are for better arrangement stated in separate part in the final of contribution. We believe, that this contribution brings for readers many interesting information and enrich readers about origin, history and the present of FIEP in Europe.